Culturable Microbial Abundance and Morphotypes in Stingless Bee Honey from Urban and Rural Landscapes - Kurnia, Fitriyan; Elpe Bibas; Muftiah Yasi Dwi Wahyuni; Marista, Etha; Raynaldo, Adityo; Rembulan, Nur Exsanty; Rara, Jani Putri; Linda, Riza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Stingless bee honey contains culturable microorganisms that may vary with floral resources, hive conditions, handling, and surrounding landscapes. This descriptive study compared total culturable counts and colony/cell morphotypes in Heterotrigona itama honey collected from one urban site in Pontianak and one rural site in Ambawang, Kubu Raya. Honey was serially diluted, cultured on Glucose Peptone Agar, and characterized using colony morphology, Gram staining, and endospore observations. Total Plate Count (TPC) values varied among isolates within each landscape: urban isolates ranged from 1.98 × 105 to 1.12 × 106 CFU/mL, while rural isolates ranged from 8.9 × 104 to 2.2 × 105 CFU/mL. Urban cultures included bacterial and yeast-like morphotypes, whereas rural cultures were represented by Gram-positive, non-spore-forming bacterial morphotypes. These observations describe culturable abundance and morphology but do not establish taxonomic identity, community diversity, or a causal landscape effect because site replication, molecular identification, physicochemical covariates, and inferential statistics were not reported. The study provides preliminary data that can guide replicated surveys combining culture-based and sequencing approaches.